Testing the application of an automatic milking system on buffalo (Bubalus bubalis) - Salvatore Faugno; Stefania Pindozzi; Collins Okello; Maura Sannino (Journal of Agricultural Engineering, 2015)
The automatic milking systems (AMS) have been deeply studied in dairy cows applications, but not in the case of buffaloes; although, a few applications to the species can be found in literature. The objective of this study is to compare some important functional aspects of AMS with the conventional milking systems. Aspects such as adaptation of buffalo to AMS and the possible relationship between milking frequency and daily milk yield were evaluated. Two groups of Bubalus bubalis were reared in the same barn, in a farm located in Piana del Sele (SA) southern Italy. Fourty primiparous buffaloes were milked using an AMS, and at the same time another herd of 40 were milked twice a day using traditional milking system (tandem). The adaptation period of buffaloes to AMS was 2 months. Milking frequency with the AMS was significantly higher compared to the one of traditional methods (2.3±0.17 times/d vs 2 times/d). Daily milk yield with the AMS was observed to be significantly higher than with traditional milking system (7.9±1.3 kg/d vs 6.9±1.06 kg/d). In this study, there was no significant relationship between the increase of daily milking frequency and daily milk yield. We can conclude that a positive AMS effect on daily milk yield and milking frequency is possible and so we can expect successful applications of the AMS to dairy buffalo farms.